The Students’ Types Error on Writing Descriptive Text (An Analysis Study at Senior High School) - Albert Efendi Pohan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
AbstractThe objective of this study is to identify the types of error and the dominant error which made by students’ on writing descriptive text. The method which applied of this research is descriptive qualitative. The subject of the study is tenth grade which consist 31 students. Data was collected by portfolio and analyzed by descriptive method to describe the students error by the formula of percentage which the number of error were divided the total number of error then multiply to 100 as constant number. The result of the research there was 357 errors in writing descriptive text. There were 25.21% with number 90 errors of spelling, 22.69% with number 81 errors of capitalization, 12.88% with number 46 errors of word choice, 9.24% with number 33 errors of singular-plural, 8.68% with number 31 errors of add or omit a word, 8.68% with number 31 errors of meaning not clear, 6.16% with number 22 errors of verb tense, 1.96% with number 7 errors of punctuation, 1.96% with number 7 errors of article, 1.68% with number 6 errors of word order, 0.28% with number 1 error of run-on sentence, 0.28% with number 1 error of word form, 0.28% with number 1 error of incomplete sentence. The dominant error which made by students on writing descriptive text was 25.21% with number 90 errors of spelling.